Adolescent body mass index and changes in pre-pregnancy body mass index in relation to risk of gestational diabetes. (December 2021) - Chodick, Gabriel; Omer-Gilon, Maayan; Derazne, Estela; Puris, Gal; Rotem, Ran; Tzur, Dorit; Pinhas-Hamiel, Orit; Cukierman-Yaffe, Tali; Shina, Avi; Zucker, Inbar; Tirosh, Amir; Afek, Arnon; et al.
Abstract: Background: Pregestational excessive body mass index (BMI) is linked to an increased risk for gestational diabetes mellitus (GDM), but less is known on the effect of adolescent BMI on GDM occurrence. The study aimed to investigate possible associations of adolescent BMI and changes in BMI experienced before first pregnancy, with gestational diabetes risk. Methods: This retrospective study was based on linkage of a military screening database of adolescent health status (Israel Defence Forces) including measured height and weight, with medical records (Maccabi Healthcare Services, MHS) of a state-mandated health provider. The latter covers about 25% of the Israeli population; about 90% of pregnant women undergo screening by the two-step Carpenter-Coustan method. Adolescent BMI was categorized according to Center of Disease Control and Prevention percentiles. Only first documented pregnanies were analyzed and GDM was the outcome. Findings: Of 190, 905 nulliparous women, 10, 265 (5.4%) developed GDM. Incidence proportions of GDM were 5.1%, 6.1%, 7.3%, and 8.9% among women with adolescent normal BMI, underweight, overweight, and obesity (p<0.001), respectively. In models that accounted for age at pregnancy, birth year, and sociodemographic variables, the adjusted odd ratios (aORs) for developing GDM were: 1.2 (95%CI, 1.1-1.3), 1.5 (1.4-1.6), and 1.9 (1.7-2.1) for adolescent underweight, overweight, and obesity (reference group, normal BMI). Adolescent BMI tracked with BMI notes in the pre-pregnancy period (r=63%). Resuming normal pre-pregnancy BMI from overweight or obesity in adolescence diminished GDM risk, but this diminished risk was not observed among those who returned to a normal per-pre-pregnancy BMI from being underweight in adolescence. Sustained overweight or obesity conferred an aOR for developing GDM of 2.5 (2.2-2.7); weight gain from adolescent underweight and normal BMI to pre-pregnancy excessive BMI conferred aORs of 3.1 (1.6-6.2) and 2.6 (2.2-2.7), respectively. Interpretation: Change in BMI status from adolescence to pre-pregnancy may contribute to GDM risk. Identifying at-risk populations is important for early preventive interventions. Funding: None.